2010
DOI: 10.1111/j.1439-0531.2008.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition During Foetal and Post-Natal Life Affects Testicular Structure and Reduces the Number of Sertoli Cells in the Adult Rat

Abstract: To test whether undernutrition during foetal to pre-pubertal life would have long lasting effects on testicular histology in adult male offspring, eleven adult Sprague-Dawley pregnant rats were divided into two groups: Control group, n = 4, fed ad libitum, during gestation and lactation (until 25 day post-partum). Underfed group pregnant females (n = 7) were kept in cages where only dams had access to food (standard rat chow, 33.5% of ad libitum intake of Control group pregnant dams). After parturition, litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 16 publications
2
24
0
3
Order By: Relevance
“…Indeed, the change in maternal diet occurred at the beginning of testicular inguinal migration in fetuses (about 270 days of gestation) [77], when testicular differentiation is still regulated. Indeed, in rats and sheep, maternal undernutrition reduced seminiferous tubule diameter and Sertoli cell numbers per tubule [24,25,78]. Another hypothesis would have been an effect of hormones: T3, leptin, insulin and IGF-1 plasma concentrations are known to increase with improved nutritional status in the fetus and neonate [31,79].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the change in maternal diet occurred at the beginning of testicular inguinal migration in fetuses (about 270 days of gestation) [77], when testicular differentiation is still regulated. Indeed, in rats and sheep, maternal undernutrition reduced seminiferous tubule diameter and Sertoli cell numbers per tubule [24,25,78]. Another hypothesis would have been an effect of hormones: T3, leptin, insulin and IGF-1 plasma concentrations are known to increase with improved nutritional status in the fetus and neonate [31,79].…”
Section: Discussionmentioning
confidence: 99%
“…This condition is defined by a deficiency of energy and nutrients over a period of several years that frequently impairs the growth and development of the child into adulthood [1,2]. Evidence that reproductive maturation and function are influenced by malnutrition is now emerging from animal studies and human populations [35]. It has been demonstrated that undernutrition during the fetal to pre-pubertal period is accompanied by changes in testicular structure with a consequent decrease in daily sperm production [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported in rats that undernutrition from the fetal period to puberty was associated with lower testicular weight and lower Sertoli cell numbers in adult life, showing that nutrition during fetal to early postnatal life may be critical to male reproductive life in adulthood [57]. Altogether, these results indicate that Sertoli cells may be particularly vulnerable to maternal undernutrition during pregnancy.…”
Section: Effects On Fertility and Gamete Quality In Adulthoodmentioning
confidence: 89%